Influence of Inventory Returns Management on Performance of Food and Beverage Manufacturing Firms in Kenya - Stephen Mutiso; Catherine Gatari (Britain International for Academic Research (BIAR) Publisher, 2023)
The purpose of the study was to assess the influence of inventory returns management on performance of food and beverage manufacturing firms in Kenya. Descriptive research design was adopted because it allowed an in-depth study of the subject. The target population was heads of procurement in the food and beverage manufacturing firms in Kenya. A sample of 132 food and beverage manufacturing firms was arrived at out of a total of 197 food and beverage manufacturing firms. R square value of 0.6 means that 60% of the corresponding variation in food and beverage manufacturing firms in Kenya can be explained or predicted by (refurbishment management, materials re-use management, waste management and re-manufacturing management) which indicated that the model fitted the study data. The results of regression analysis revealed that there was a significant positive relationship between dependent variable and independent variable at (β = 0.6), p=0.000 <0.05). The findings of the study concluded that refurbishment management, materials re-use management, waste management and re-manufacturing management have a positive relationship with performance of food and beverage manufacturing firms in Kenya. The study recommended that food and beverage manufacturing firms should embrace inventory returns management aspects so as to improve performance and further researches should to be carried out in other firms to find out if the same results can be obtained.